(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
A field experiment was carried out at the Agricultural Research Station of the College of Agriculture - University of Basrah during the winter season of 2021-2022 to study the effect of adding different rates of triple superphosphate fertilizer compared to Nano-phosphate fertilizer on the vegetative growth components of wheat (Triticum aestivum L.). Triple super phosphate fertilizer at rates 0, 30, 60 and 90 kg P ha-1 was applied to soil at planting, while Nano-phosphate fertilizer at rates 0, 5, 10 and 15 kg P ha-1 was added as a foliar on the plant at the stages of branching and elongation, Height of the plant and flag leaf area at the flowering stage, the number of days from planting to 50% heading, and from 50% heading to full maturity, and the dry weight of the plant was measured at the 50% heading stage. The results showed no significant differences in the studied traits (plant height, flag leaf area and The number of days from planting to 50% heading and from 50% heading to full maturity and dry weight) between the two sources of phosphate fertilizer despite the added amount of Nano-fertilizer representing (1/4) of the amount of triple superphosphate fertilizer, and the results also indicated that the increase in phosphorous rates from of 0 to 90 kg of triple superphosphate and from 0 to 10 kg of P ha-1 of Nano phosphate fertilizer led to an increase in growth parameters, but increasing Nano fertilizer to 15 kg of P ha-1 reduced in all growth parameters. The results also indicated the superiority of the Ibaa99 cultivar in the characteristics (plant height and number of days from planting to 50% heading and dry weight), while the Jad cultivar was superior in traits (flag leaf area and number of days from 50% heading to full maturity).